(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
DDoS assaults provide a substantial risk to the accessibility and dependability of cloud-based online services, affecting corporations, organizations, and individuals. Conventional DDoS defense methods are frequently ineffective in cloud settings because of their ever-changing characteristics and the financial consequences of service interruptions. This article introduces a proposed architectural solution to reduce DDoS assaults on a cloud-hosted application. This design relies on creating a duplicate of the application in a cloud environment and directing only valid requests to this duplicate. The suggested architecture may filter valid traffic without the requirement to identify hostile consumers, therefore avoiding the associated burden and potential mistakes.